PENGEMBANGAN APLIKASI MOBILE SISTEM INFORMASI PRODUK PERTANIAN KABUPATEN BULELENG - Luh Joni Erawati Dewi; I Nyoman Saputra Wahyu Wijaya; Ketut Agus Seputra (SINTECH (Science and Information Technology) Journal, 2022)
The availability of accurate and up-to-date agricultural data is very much needed for agricultural development in Buleleng district. This data requirement can be facilitated by utilizing information and communication technology. The purpose of this research is to create a mobile-based Agricultural Product Information System (SIPROTANI) application. The SIPROTANI mobile application was developed following the agile software development model scrum. The data requirements for the system were obtained in collaboration with the Buleleng district agriculture office. Users of mobile-based SIPROTANI are Field Agricultural Extension (PPL) and administrators. Functions that have been developed in SIPROTANI are displaying and managing agricultural products in Buleleng Regency, managing farmer group data, managing farmer data, searching for agricultural product data, and displaying product reports. agriculture according to the criteria of product type, location, (range) harvest date. It is hoped that with this system, Buleleng Regency has accurate, up to date data related to agricultural products in Buleleng. In addition, this system can be used as a model for other districts in Bali and other regions in Indonesia. In the future, this system can be developed into e-commerce that connects farmers as producers and the community/stakeholders as consumers, so that the distribution chain of product marketing can be cut. Farmers will get a fair price for their products and consumers will get good quality products at a commensurate price.